Using the Service-Learning approach to bridge the gap between theory and practice in teacher education - Resch, K.; Schrittesser, I. (International journal of inclusive education, 2023)
Service-Learning stands out as a teaching approach that connects theory and practice by giving students the opportunity both to participate in a service that meets community needs and to reflect on the experience in class in order to gain a deeper understanding of the course content and an enhanced sense of civic engagement. The advantages of Service-Learning for inclusive education have recently been underpinned by studies, in which pre-service teachers are exposed to diverse population groups in schools or communities. Our study explores how Service-Learning is applied in teacher education in Austria. It is based on a series of semi-structured interviews with 13 teacher educators who apply this form of teaching in cooperative projects with schools. Our findings suggest that teacher educators distinguish between five orientations in Service-Learning (connecting theory and practice, engagement, community needs, job-related skills, learning outside the classroom), take on distinct expert and support roles, and see multiple benefits in Service-Learning. Our study underlines the importance of Service-Learning for inclusive education and the value of preparing pre-service teachers for dealing with diverse groups of pupils by allowing them to experience the real-world problems that confront schools.